2008
DOI: 10.1007/s00262-008-0542-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional efficacy of tumor-specific T cells expanded using HLA-Ig based artificial antigen presenting cells (aAPC)

Abstract: Adoptive immunotherapy for treatment of cancers and infectious diseases is often hampered by a high degree of variability in the final T cell product and in the limited in vivo function and survival of ex vivo expanded antigen-specific cytotoxic T cells (CTL). This has stimulated interest in development of standardized artificial antigen presenting cells (aAPC) to reliably expand antigen specific CTL. However, for successful immunotherapy the aAPC ex vivo generated CTL must have anti-tumor activity in vivo. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…Phenotypic characterization of aAPC-generated melanoma antigen Mart-1-specific cytotoxic T lymphocytes (CTLs) showed they were effector memory T cells (CD45RA (41). Limited functional characterization of ex vivo-generated human CD8 + T cells suggests that they can also carry out effector functions in vivo with ex vivo-generated effector memory cell migration to nonlymphoid tissues and selective homing to tumors (41,42). In addition, investigators have shown that aAPC-generated T cell lines could be maintained in culture up to 1 year without becoming terminally differentiated.…”
Section: ) Expansion Of Multifunctional Cd8 + T Cells With Modcs Imentioning
confidence: 99%
“…Phenotypic characterization of aAPC-generated melanoma antigen Mart-1-specific cytotoxic T lymphocytes (CTLs) showed they were effector memory T cells (CD45RA (41). Limited functional characterization of ex vivo-generated human CD8 + T cells suggests that they can also carry out effector functions in vivo with ex vivo-generated effector memory cell migration to nonlymphoid tissues and selective homing to tumors (41,42). In addition, investigators have shown that aAPC-generated T cell lines could be maintained in culture up to 1 year without becoming terminally differentiated.…”
Section: ) Expansion Of Multifunctional Cd8 + T Cells With Modcs Imentioning
confidence: 99%
“…These aAPC demonstrated antigen-specific T cell generation and expansion favorable to autologous dendritic cells (DC)(13,14) and were successfully tested in different in vitro systems(15–17). In vivo aAPC-generated T cells inhibited tumor growth as efficient as DC-generated T cells(18). Furthermore, adoptively transferred low affinity T cells where efficiently activated by co-administration of aAPC and subsequently lead to tumor reduction in an in vivo melanoma tumor model (19).…”
Section: Introductionmentioning
confidence: 99%
“…The use of magnetic-bead-based aAPCs was investigated in a severe combined immunodeficiency (SCID) mice bearing human melanoma tumors [68]. These mice received MART-1 specific T cells generated from human PBMC after 1 month of in vitro culture with magnetic beads presenting MART-1-loaded human MHC dimers and anti-CD28 (1:1 ratio of aAPCs to cells) [68].…”
Section: Ex Vivo Application Of Acellular Apcs For Adoptive Immunothementioning
confidence: 99%
“…These mice received MART-1 specific T cells generated from human PBMC after 1 month of in vitro culture with magnetic beads presenting MART-1-loaded human MHC dimers and anti-CD28 (1:1 ratio of aAPCs to cells) [68]. Mice bearing 2-week-old tumors received an intravenous injection of 3 × 10 6 MART-1 specific cells and IL-2 injections (2 × 10 5 IU/mouse) on days 0 and 2 following cell transfer [68]. Magnetic-bead-expanded cells were compared with cells stimulated by monocyte-derived DC.…”
Section: Ex Vivo Application Of Acellular Apcs For Adoptive Immunothementioning
confidence: 99%